The cost of privilege: masculinity, heterosexuality, and confinement of the wanting to live (Revista Rupturas, 2022)
During the last few years, the language of privilege has attained popularity as a medium of expression and registry of the radical inequalities that organize modern life. In this setting, scholars on privilege have urged people to publicly exam and make explicit their own privileges, as a necessary condition for collaboration and dialogue among the social groups that have been systematically advantaged by colonial, patriarchal, heterosexist and class hierarchies, and those who have been harmed by them. I distance myself from this proposal, to argue that the abundance of identifications with the condition of privilege and un-privilege, based on a symbolic economy of debt, shutters the possibility of political subjectification on both sides of the conversation
Keywords: Privilege; heterosexuality; masculinity; feminisms; subjectification